Trần Minh
Nguyễn Hoàng Minh
4 phút trước

\(2,\\ 1,ĐK:\left\{{}\begin{matrix}x-1\ge0\\3-x\ge0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x\ge1\\x\le3\end{matrix}\right.\\ 2,ĐK:x\ne\dfrac{1}{2}\\ BPT\Leftrightarrow2\left(x-1\right)< 2x+1\\ \Leftrightarrow2x-2< 2x+1\\ \Leftrightarrow0< 3\left(luôn.đúng\right)\)

Vậy BPT luôn đúng với mọi x

Bình luận (0)
Lấp La Lấp Lánh
3 phút trước

Bài 2:

a) \(A=\sqrt{x-1}+\sqrt{3-x}\)

\(ĐK:\) \(\left\{{}\begin{matrix}x-1\ge0\\3-x\ge0\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}x\ge1\\x\le3\end{matrix}\right.\) \(\Leftrightarrow3\ge x\ge1\)

b) \(\dfrac{x-1}{2x+1}< \dfrac{1}{2}\)

\(\Leftrightarrow2\left(x-1\right)< 1\left(2x+1\right)\)

\(\Leftrightarrow2x-2< 2x+1\)

\(\Leftrightarrow-2< 1\left(đúng\forall x\right)\)

Vậy \(x\in R\)

Bình luận (1)
Nguyễn Hoàng Minh
2 phút trước

\(44,\\ 3\sqrt{5}=\sqrt{3^2\cdot5}=\sqrt{45}\\ -5\sqrt{2}=\sqrt{\left(-5\right)^2\cdot2}=\sqrt{50}\\ -\dfrac{2}{3}\sqrt{xy}=\sqrt{\left(-\dfrac{2}{3}\right)^2xy}=\sqrt{\dfrac{4}{9}xy}\\ x\sqrt{\dfrac{2}{x}}=\sqrt{\dfrac{2x^2}{x}}=\sqrt{2x}\)

Bình luận (0)

Khoá học trên OLM của Đại học Sư phạm HN